The energy effects of the two-stage cooling use in the air-conditioning unit of operating theaters of hospitals - Jakubiak, Monika; Porowski, Mieczysław (Instal, 2020)
The article presents an analysis of the unit demand for net, final and primary energy for an air-conditioning unit with one-stage or two-stage cooling in an application for a hospital operating theater. As a tool in the optimization procedure, a simulation model of the air conditioning system operation during the whole year was formulated. Among other things, the electricity demand for cold generation in cooling water generators was determined. The calculation results for the case study show that the use of two-stage cooling in the air-conditioning unit of the air conditioning system allows to reduce the demand for electricity for the production of cooling by about 19% compared to single-stage cooling.
Keywords: air conditioning of operating theaters; optimal energy efficiency control